Pengaruh Kepemimpinan Terhadap Kinerja Karyawan pada PT. Malea Energy Di Makale Selatan Kabupaten Tana Toraja. - Tangkeallo, Dian Intan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Human resources are resources that are no less important in a company. As movers, human resources must have standards. The success or failure of a company in achieving its goals depends on the success of its human resources in carrying out their duties. The success of employees in carrying out their duties is supported by their performance. To achieve the expected goals, an employee must perform well. Performance is the result of the work produced by an employee. Therefore, the organization always strives to create employee performance. The purpose of this study was to determine the effect of leadership on the performance of PT. Malea Energy. This is an example of quantitative research. This study's population consists of 30 PT. Malea Energy employees. The determination of the sample is based on saturated samples, namely, all populations are used as samples, so the number of samples in this study is 30 employees. The data analysis technique is simple linear regression with the help of SPSS. The results of the study found that leadership has a positive and significant effect on the performance of employees at PT. Malea.